Defining Endoscopic Remission in Ileocolonic Crohn's Disease: Let's Start from Scratch. (6th July 2018) - Bossuyt, Peter; Louis, Edouard; Mary, Jean-Yves; Vermeire, Séverine; Bouhnik, Yoram
Abstract: Endoscopic remission is the cornerstone of drug development and the guidance for daily clinical practice in Crohn's disease [CD]. However, although scoring systems for endoscopic activity in CD have been available for more than three decades, no consensus exists on the definition of endoscopic remission. In this viewpoint we describe the shortcomings of the current definition of endoscopic remission in ileocolonic CD and the essential requirements for a newly developed endoscopic scoring tool for endoscopic remission in CD.